Csodás barátságok kezdete: A kelet-afrikai regionális biztonsági komplexum határainak átalakulása a 21. században - Marsai, Viktor (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
Nowadays, the East African Regional Security Complex (RSC) is going trough a radical reshaping: we can observe an increasing interdependency among the countries of the region and the expanding boundaries of the RSC which are deeply affected by the political and security processes of the Arabian Peninsula, North and Southern-East Africa. Although it is too early to declare the birth of a new RSC, it is obvious that the original geographic frameworks of the analysis are not sustainable any more.